Handheld Reflectance Confocal Microscopy to Aid in the Management of Complex Facial Lentigo Maligna - Hibler, Brian P. (Cutis, 2017)
Diagnosis and management of lentigo maligna (LM) and LM melanoma (LMM) is challenging. Novel noninvasive imaging technologies such as reflectance confocal microscopy (RCM) have advanced the ability to better diagnose and monitor challenging lesions. In addition, the new handheld RCM (HRCM) together with the use of videomosaics has allowed an accurate evaluation of large lesions in concave/convex areas of the body (eg, the face). Herein, we review the impact of HRCM in the detection, treatment decision-making, and monitoring of 5 cases of complex facial LM/LMM. In the cases presented, HRCM enabled the detection of subclinical margins, presence of invasion, detection of persistence/recurrence, and monitoring of surgical and nonsurgical therapies. In this preliminary report, our results suggest that HRCM is a versatile ancillary tool in pretreatment decision-making, intraoperative surgical mapping, and posttreatment monitoring of complex facial LM/LMM.